(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
It has been reported that external pressure exerted on lower limbs helps to accelerate blood flow during doing exercise or playing sports and thus improving sports performance. In this paper, the pressure effect on skin blood flow was investigated. Pressures of various magnitudes were exerted on ankles and calves respectively by using a sphygmomanometer, under which the skin blood flow change was observed. The results showed that the skin blood flow increased when pressure of certain level was loaded at ankle or calf; however, as the pressure magnitude exceeding certain value, it turned to decrease. Moreover, ankles seemed to bear much higher pressure than calves. The mechanism of skin blood flow responding to external pressure was also discussed.